870 μm continuum observations of the bubble-shaped nebula Gum 31 - Duronea, Nicolás Urbano (2015)
Aims. We present here a study of the cold dust in the close environs of the ring nebula Gum 31. We aim at deriving the physical properties of the molecular gas and dust associated with the nebula, and investigating its correlation with the star formation in the region, which was probably triggered by the expansion of the ionization front against its environment. Methods. We make use of 870 μm emission data obtained with the Large APEX Bolometer Camera (LABOCA) to map the dust emission. The 870 μm emission provides an excellent probe of mass and density of dense molecular clouds. The obtained LABOCA image was compared to archival infrared, radio continuum, and optical images. Results. The 870 μm emission follows the 8 μm (Spitzer), 250 μm, and 500 μm (Herschel) emission distributions showing the classical morphology of a two-dimensional projection of a spherical shell. We use the 870 μm and 250 μm images to identify 60 dust clumps in the collected layers of molecular gas using the Gaussclumps algorithm. The clumps have effective deconvolved radii between 0.16 pc and 1.35 pc, masses between 70 M⊙ and 2800 M⊙, and volume densities between 1.1 × 103 cm-3 and ~2.04 × 105 cm-3. The total mass of the clumps is ~37 600 M⊙. The dust temperature of the clumps is in the range from 21 K to 32 K, while inside the Hii region it reaches ~40 K. The clump mass distribution for the sample is fitted by a power law dN/dlog (M/M⊙) ∝ M-α, with α = 0.93 ± 0.28. The slope differs from those obtained for the stellar IMF in the solar neighborhood, suggesting that the clumps are not direct progenitors of single stars/protostars. The mass-radius relationship for the 41 clumps detected in the 870 μm emission shows that only 37% of them lie in or above the high-mass star formation threshold. Most of this 37% have candidate YSOs projected inside their limits. A comparison of the dynamical age of the Hii region with the fragmentation time, allowed us to conclude that the collect-and-collapse mechanism may be important for the star formation at the edge of Gum 31, although other processes may be acting simultaneously. The position of the identified young stellar objects in the region is also a strong indicator that the collect-and-collapse process is acting.